Hacia una etnografía del comienzo en la praxis de los profesores de educación física - Salvá, Nancy (2024)
This article presents research advances on how graduates in Physical Education learn to became teachers in their first five year of professional practice at the Higher Institute of Physical Education (ISEF) (Uruguay). The introduction describes the formation of university physical education. The first scenario develops conceptual approaches to pedagogical praxis, specially, in physical education. The second is based on the ethnographic approach to educational research and the epistemological, methodological and political shifts that it implies. The third presents a reflective and rhizomatic analysis of initial approaches to narrative identities of young teachers that arise from the first advance in field work. Finally, it ventures into the labyrinth of research to develop some reflections and possible projections.